Influence of particle size and fibre content on the dimensional stability and mechanical behaviour of composites produced from cordiamillenii and recycled polyethylene (2020)
The degradation of the environment by wood and plastic wastes has continued to attract serious attention. Utilisation of these wastes without additives and pre-treatment for the production of wood plastic composites will give credence to the fundamentals of compatibility and performance of the composites and also for economic reasons. Therefore, this study was designed to investigate the dimensional stability and strength properties of wood plastics composites produced from wastes of Cordiamillenii and recycled polyethylene at a target density of 920kg/m3. Three levels of wood particle size (0.0< 0.25, 0.25≤ 1.0 and 1.0<2.0), three levels of wood/plastics ratio (30:70, 40:60 and 50:50) and three types of recycled polyethylene (LDPE, HDPE and LDPE/HDPE) were applied. The dimensional stability (Water Absorption (WA), thickness swelling (TS) and Linear Expansion (LE)) and strength properties (Modulus of Elasticity (MOE) and Modulus of Rupture (MOR)) were examined. The mean range of results obtained for the sorption properties (WA; 1.6-10.2%, TS; 0.14-2.07% and LE; 0.11-0.37%) indicated the composites are dimensionally stable. The mean strength properties values (MOE; 0.24-1.81GPa and MOR; 6.55- 15.87MPa) compared favourably with those reported in literature. The composites produced with HDPE at 30% wood content had higher strength and lower sorption properties than other formations. Particle sizes, plastics types and mixing ratio had significant effect the dimensional stability and mechanical behaviour of the composites at α0.05 significance level. Acceptable WPCs were produced from Cordiamillenii wastes and recycled polyethylene for non-structural applications.